Assessment of nutrients in Bued River - Joble, Alyssa Joyce L.; Mawirat, Sherylyn C.; Resurreccion, Augustus C.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
Nutrients released in excessive amounts pollute water bodies. In this study, the nutrient concentration in Bued River, specifically nitrate and phosphate, were examined. Water samples trom the 13 established surface water sampling locations and identified waste water sources along the river were tested and analyzed. Different physico-chemical properties of water were also measured in these locations. The results were presented in maps showing the locations of the identified nutrient point sources and surface water sampling locations with the monthly nutrient concentrations. Nutrient concentration and other water quality parameters were correlated through statistical analysis. Nitrate and phosphate displayed a significant correlation which suggested that pollutant sources released both nutrients. High nutrient concentrations were observed in sampling points that are developed and relatively have higher number of inhabitants. It was also found out that the nutrient concentration is independent with the flow rate of the river. Furthermore, acquired nutrient concentration results were assessed using existing local and international standards. The nitrate concentration of the surface water passed the standards set by DENR Administrative Order No. 34, US Environmental Protection Agency, World Health Organization, Malawi Bureau of Standards and Canadian Water Quality Guidelines; while, the phosphate concentration showed failing percentages based from the standard set by DAO 34 and US EPA.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Nutrient pollution of water